Considering Modern Shia Thoughts on Religious Harmony: Husain Faḍlullah’s Contribution in Min Waḥy al-Qur’an - Fawaid, Ahmad; Hidayatullah, Adi Rahmat (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2023)
This article aims to reveal Muhammad Husein Faḍlullah’s ideas about Religious Harmony as contained in his commentary, min waḥy al-Qur’an. Faḍlullah’s thoughts are relevant to study in the current context to see the concept of harmony from a different perspective, namely the Modern Shia school. By using a qualitative paradigm with a critical discourse analysis approach to Faḍlullah’s works, this study found two findings: first, Modern Shia consistently offers the concept of Ijtimā’ī Adabī interpretation, which is centered on the ideas of tolerance, harmony between religious communities, social holiness, and rejection against all forms of radicalism; second, Interpretation products are inseparable from ideological ideas and teachings of their schools. At this point, even though Faḍlullah is involved in the political movement of the Hezbollah Party, which tends to be radical, his thoughts still represent his school of thought, especially regarding religious tolerance and harmony. From these findings, this study also wants to emphasize that a person's background does not directly influence the product of his thoughts in the future, as stated by Naṣr Ḥamid Abū Zayd. This research supports Andrew Silke and Tinka Veldhuis’s findings regarding “Countering violent extremism in prisons: A review of key recent research and critical research gaps” that the author's personal character and personal experience factors determine the product of one’s interpretation.